Study of the ablative properties of phenolic/carbon composites modified with mesoporous silica particles. (December 2018) - Asaro, L; Manfredi, LB; Rodríguez, ES
Mesoporous silica particles and carbon black were selected as fillers for a resol-type phenolic resin, to be used as a matrix for ablative materials. Composites were processed with the modified polymer and carbon fibers were used as continuous reinforcement. The ablative properties of the materials obtained were studied by the oxyacetylene torch test and the ablated samples were observed by scanning electron microscopy. Composites with 30 wt. % of carbon black achieved the lowest linear erosion rate and the highest insulation index, denoting the ability of the char produced to protect the virgin material. Considering that such composite has 44% by volume of carbon fibers, it could be inferred that its properties could be improved by increasing the fiber content and maintaining the amount of carbon black. The composite with 20 wt. % of mesoporous silica particles exhibited the lowest mass erosion rate, indicating a better stabilization of the char. Regarding dynamic-mechanical properties, the addition of particles induced a decrease in the modulus and glass transition temperature of all the systems studied.